IMPLEMENTASI MODEL PEMBELAJARAN AJAK TEMANI MANDIRI (MPATM) BERBASIS AJARAN KETAMANSISWAAN DI SEKOLAH DASAR - Nisa, Ana Fitrotun; Nizhomi, Bestiana; Yuniharto, Bonifatius Sigit; Krisnajati, Endah (Jurnal Terapan Abdimas, 2023)
Abstract. Curriculum development is an important step for the government in improving human resources in Indonesia. The independent curriculum policy changed the perspective of educational actors, especially school principals and teachers. Educational actors are the vanguard in the successful implementation of the independent curriculum, but they have limited references in implementing their curriculum. These complaints were then answered by the service team through community service activities by providing training related to the implementation of the self-accompanied learning model (MPATM) based on Tamansiswa teachings. The objectives of this activity include being able to increase teacher understanding regarding Tamansiswa teachings which are implemented through MPATM and being able to increase innovation and competence of elementary school teachers in implementing the independent curriculum in learning. Community service activities are carried out on August 9-10 2022 with the target of SD teachers at Jetis using the offline method, namely through the stages of socialization, development, implementation and evaluation. Through this activity, school principals and elementary school teachers at Jetis gained additional new knowledge related to learning innovations with MPATM which are integrated with the independent curriculum. Teachers are also able to innovate in learning tools and implemented in the learning process. The results of the evaluation showed that with this activity the tutors (teachers and principals) were more enthusiastic about carrying out learning activities based on Tamansiswa teachings and at the same time as an effort to re-ground Tamansiswa teachings in the independent curriculum so that meaningful learning was created.Abstrak. Pengembangan kurikulum menjadi langkah penting pemerintah dalam memperbaiki sumber daya manusia di Indonesia. Kebijakan kurikulum merdeka mengubah cara pandang para pelaku pendidikan khususnya kepala sekolah dan guru. Pelaku pendidikan sebagai garda depan dalam mensukseskan implementasi kurikulum merdeka, namun mereka memiliki keterbatasan referensi dalam mengimplementasikan kurikulum meredeka. Keluhan tersebut kemudian dijawab oleh tim pengabdi melalui kegiatan pengabdian masyarakat dengan memberikan pelatihan terkait implementasi model pembelajaran ajak temani mandiri (MPATM) berbasis ajaran tamansiswa. Tujuan kegiatan ini diantaranya adalah mampu meningkatkan pemahaman guru terkait ajaran tamansiswa yang diimplementasikan melalui MPATM dan mampu meningkatkan inovasi serta kompetensi guru SD dalam mengimplementasikan kurikulum merdeka dalam pembelajaran. Kegiatan pengabdian masyarakat dilaksanakan pada tanggal 9-10 Agustus 2022 dengan sasaran Guru SD di Jetis dengan metode luring yaitu melalui tahapan sosialisasi, pengembangan, implementasi dan evaluasi. Melalui kegiatan ini, kepala sekolah dan guru SD di Jetis memperoleh tambahan ilmu baru terkait inovasi pembelajaran dengan MPATM yang terintegrasi dengan kurikulum merdeka. Guru juga mampu menginovasikannya dalam perangkat pembelajaran dan diimplementasikan dalam proses pembelajaran. Hasil evaluasi yang dilakukan menunjukkan bahwa dengan kegiatan ini pamong (guru dan kepala sekolah) semakin bersemangat melakukan kegiatan pembelajaran yang berbasis ajaran tamansiswa dan sekaligus sebagai upaya membumikan kembali ajaran tamansiswa dalam kurikulum merdeka sehingga tercipta pembelajaran yang bermakna.